Potent anti-inflammatory responses: Role of hydrogen in IL-1α dominated early phase systemic inflammation - Youzhen Wei; Youzhen Wei; Youzhen Wei; Kun Wang; Yafang Zhang; Yi Duan; Yan Tian; Hongling Yin; Xuelian Fu; Zuan Ma; Jianjun Zhou; Min Yu; et al. (Frontiers in Pharmacology, 2023)
Introduction: It has been proven that hydrogen has obvious anti-inflammatory effects in animal experiments and clinical practice. However, the early dynamic process of the inflammatory response caused by lipopolysaccharide (LPS) and the anti-inflammatory effect of hydrogen has not been definitively reported. Methods: Inflammation in male C57/BL6J mice or RAW264.7 cells was induced with LPS, for which hydrogen was immediately administered until samples were taken. Pathological changes in lung tissue were assessed using hematoxylin and eosin (HE) staining. Levels of inflammatory factors in serum were determined using liquid protein chip. The mRNA levels of chemotactic factors in lung tissues, leukocytes, and peritoneal macrophages were measured by qRT-PCR. The expression levels of IL-1α and HIF-1α were measured by immunocytochemistry. Results: Hydrogen alleviated LPS-induced inflammatory infiltration in the lung tissues of mice. Among the 23 inflammatory factors screened, LPS-induced upregulation of IL-1α etc. was significantly inhibited by hydrogen within 1 hour. The mRNA expression of MCP-1, MIP-1α, G-CSF, and RANTES was inhibited obviously by hydrogen at 0.5 and 1 h in mouse peritoneal macrophages. In addition, hydrogen significantly blocked LPS or H2O2-induced upregulation of HIF-1α, and IL-1α in 0.5 h in RAW264.7 cells. Discussion: The results suggested that hydrogen is potentially inhibitive against inflammation by inhibiting HIF-1α and IL-1α release at early occurrence. The target of the inhibitive LPS-induced-inflammatory action of hydrogen is chemokines in macrophages in the peritoneal cavity. This study provides direct experimental evidence for quickly controlling inflammation with the translational application of a hydrogen-assisted protocol.